Challenges of MARA female educators in the era of globalization - Salleh, Mohamad Johdi (ERPA Trust, 2015)
This study discusses on the issue of teachers and lecturers in the field of education to produce effective students who are successful, competent and moral. It analyzes the respondents’ knowledge on the definition of globalization and the effectiveness of their efforts to face the challenges of globalization era. The respondents were 150 female educators from the Maktab Rendah Sains MARA (MRSM), Institut Kemahiran MARA (IKM), Kolej MARA (KM), Kolej Profesional MARA (KPM), and, Kolej Kemahiran Tinggi MARA (KKTM), Malaysia. The data was collected through a set of questionnaire distributed to the respondents. The results show, 100% of the respondents have ‘heard of globalization’. 79.4% of them were ‘challenged in the globalization era’. They agreed that one of the challenges was ‘Globalization is a major cause of students’ disciplinary problems now. Surprisingly, 95.3% of them admitted that the ‘Challenges of present teachers are more severe than before’. Moreover, the respondents were more challenged when ‘the Students today are more advanced than those teachers with the knowledge of information technology’ with 91.4% of agreement. The respondents were in a real challenged when 100% of them requested that the ‘PTA should jointly address the problem of globalization in education’. In fact, this study is intended to provide information and description to relevant parties in the education sectors to overcome the existing problems in order to strengthen the educational system in providing a harmonic path and beneficial to professional educators for the purpose of their well-beings, faith and professionalism in the challenges of globalization.